Mechanisms of cooperativity and allosteric regulation in proteins - Perutz, Max (CAMBRIDGE UNIVERSITY PRESS, 1990)
In this book Max Perutz, who won the Nobel Prize in 1962 for his work on the structure of haemoglobin, shows how the functions of several allosteric proteins can be understood on the basis of their molecular mechanisms.